Kajian Eksistensialisme Dalam Cerpen “Tujuan Negeri Senja” Karya Seno Gumira Ajidarma - Maulfinnizar Haular Rosul; Theresia Meturan (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This article aims to analyze the short story Destination of the Land of Twilight through the lens of contemporary existentialist theories, focusing on the concepts of freedom, anxiety, and absurdity. Through this approach, this article will explore how these themes appear in short stories and how the main character faces them in his life journey full of uncertainty. By connecting these contemporary theories with literary works, this article is expected to provide deeper insights into the interaction between literature and philosophy in describing the existential condition of humans in the modern world. This study uses a qualitative descriptive analytical approach to analyze the short story The Purpose of the Land of Senja by Seno Gumira Ajidarma through the lens of existentialist philosophy. The main focus of this research is to explore the philosophical themes contained in short stories, such as freedom, anxiety, and absurdity, which are concepts in existentialism. The theoretical approach used draws on the thought of contemporary philosophers, such as Michel Foucault, Alain de Botton, and Jean-Luc Nancy, to examine how these short stories reflect the human experience of uncertainty and the search for meaning in life. The data collection technique is carried out by text study, namely reading and reviewing short stories in depth to identify elements that reflect existential themes, as well as relevant literature reviews. The short story The Purpose of the Land of Senja by Seno Gumira Ajidarma depicts the existential journey of a protagonist who is trapped in the search for the meaning of life. The main character in this short story is depicted in a state of confusion, questioning the purpose of his life and the world around him. This search, which is depicted with the metaphor of "Land of Twilight", reflects the anxiety and uncertainty that is at the heart of existentialism.